Causal Mechanisms in the Global Development of Social Policies - Kuhlmann, Johanna; Nullmeier, Frank (Global Dynamics of Social Policy,, 2022)
Critical in policy analysis is not only the question whether it works. One needs to know *how* it works. This is a question about causal mechanisms. In this exemplary volume the authors provide some generic mechanisms that can apply in variety of settings along with detailed case studies of mechanisms in individual countries. It is essential reading for all those interested in social policy. - Gary Goertz, University of Notre Dame, USA Causal mechanisms meet social policy research in this masterful volume that offers clear theoretical and methodological guidance, while providing concrete examples from across the world. Kuhlmann, Nullmeier, and the impressive group of scholars they have gathered offer an innovative mechanism-based approach to study social policy processes that elegantly fuses the actions of policy actors with complex theory-centered causal sequences. This book's theoretical and methodological insights make it a must-read for social policy scholars across disciplines. - Sara Niedzwiecki, University of California, Santa Cruz, USA This open access edited volume introduces the concept of causal mechanisms to explore new ways of explaining the global dynamics of social policy, and shows that a mechanism-based approach provides several advantages over established approaches for studying social policy. The introductory chapter outlines the mechanism-based approach, which stands out by modularisation and a clear focus on actors. The mechanism-based approach then guides the twelve chapters on social policy developments in different Asian, African, European and Latin American countries. Based on these findings, the concluding chapter provides a structured compilation of causal mechanisms and outlines how a mechanism-based approach can further strengthen research on the global development of social policies, especially in a comparative perspective. The edited volume is highly relevant for social policy scholars from a variety of disciplines, as well as for scholars interested in strengthening explanation in the social sciences. Johanna Kuhlmann is Postdoctoral Researcher at the SOCIUM Research Center on Inequality and Social Policy, University of Bremen, Germany. Frank Nullmeier is Professor of Political Science at the SOCIUM Research Center on Inequality and Social, University of Bremen, Germany.